Indenização punitiva e o dano extrapatrimonial na disciplina contratual - Marinangelo, Rafael (2016)
The purpose of this study is to defend the application of punitive damages, which are similar to punitive damages in the American legal system, in cases of contractual breach committed intentionally or with gross negligence, when profits are earned from the wrongdoing, and from which arises non-economic damages to the non-breaching party. The intended goal is justified by the constant cases of non-performance of contract, which often consists in expedients intentionally committed to obtain a financial gain on disregard for the non-pecuniary rights of the counterpart. As the compensation for material and nonpecuniary damages, whose amount is modest and relatively predictable, is easily included in the calculations of those who want to profit from other people’s damage, the proposal is to encourage reflection on the roles to be played by punitive damages in the regulation and restoration of an ethical human coexistence. For that purpose, foreign and national articles were consulted in order to bring up the hypothesis of application of punitive damages in the common and civil law systems, as well as in the Brazilian legal system. We made studies on the economic theories of law and the most current contract theories, examining them in view of the most relevant constitutional aspects of the matter, as well deepened the study on the dignity of the individual and social ethics involved, highlighting their importance on the justification of a more stringent treatment, as expressed in punitive damages. As a result, we observed a widespread acceptance of the compensation of non-economic damages arising from the contract, as well as the application of punitive damages as a mechanism to prevent, repress and dissuade wrongdoings committed intentionally or with gross negligence, which patently violate the rights of others and the dearest values of a society based on the principles of democratic rule of law